2018
DOI: 10.14444/5087
|View full text |Cite
|
Sign up to set email alerts
|

Role of Bisphosphonates as Adjuvants of Surgery in Giant Cell Tumor of Spine

Abstract: Background: The role of bisphosphonates is well established in giant cell tumor of bone (GCTB) of extremities, but its role in spine GCTB is still not established. Our main purpose was to evaluate the role of bisphosphonates in spinal GCTB with the help of radiologic assessment.Methods: A retrospective analysis of all spine GCTB patients who underwent an operation from July 2005 to January 2014 was done. Patients of spine GCTB in whom bisphosphonates were given constituted the study group. This group was compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…[ 10 ] Moreover, other studies have shown that neurological pain is also a salient feature of GCTB. [ 15 ] All patients in the present study experienced local pain, and 1 patient demonstrated a neurogenic bladder. Local pain is one of the most prominent complaints in patients with spinal GCTB, needing swift and effective pain management, regardless of age.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…[ 10 ] Moreover, other studies have shown that neurological pain is also a salient feature of GCTB. [ 15 ] All patients in the present study experienced local pain, and 1 patient demonstrated a neurogenic bladder. Local pain is one of the most prominent complaints in patients with spinal GCTB, needing swift and effective pain management, regardless of age.…”
Section: Discussionmentioning
confidence: 80%
“…[ 14 ] However, some studies reported favorable outcomes after treatment with a combination of surgical treatment and adjuvant drug therapy. [ 9 , 10 , 15 , 20 ] The typical drug prescribed is denosumab. [ 9 , 20 , 21 ]…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed studies on aggressive GCT published over the past 20 years according to PRISMA statement, and 52 studies were involved ( Figure 10 ). 15 - 66 There were 60 patients with 53 CT scans and 39 MRI scans, of whom 21 patients underwent enhanced scans simultaneously. The typical and atypical features were summarized according to the diagnostic standards in the present study ( Table 2 ) and the frequency of the features was similar.…”
Section: Resultsmentioning
confidence: 99%
“… 18 , 19 ) However, the efficacy and safety of denosumab treatment after surgery to prevent recurrence have not been fully established. 20 ) Bisphosphonate is another possible postoperative adjuvant treatment; 21 ) it inhibits osteoclast activity and has been shown to significantly prolong progression-free survival after subtotal resection for GCT. 22 ) Although the treatment strategy presented here is by no means the best, it may be helpful for surgeons to make a surgical plan assuming postoperative pharmacological therapy before surgery.…”
Section: Discussionmentioning
confidence: 99%